Application of Morishita Spread Index in the study of landslides from the Kulekhani watershed, central Nepal - Dhar, Mahesh Singh; Dhital, Megh Raj (Journal of Nepal Geological Society, 2004)
The Kulekhani watershed was severely affected by sedimentation, landslides, and gully erosion in 1993. The sediments produced were ultimately supplied to the reservoir decreasing its gross storage capacity. A statistical tool, called Morishita Spread Index, was applied to detect the landslide distribution pattern in the watershed. Morishita Spread Index was greater than 1 and decreased with increasing mesh scale. Such a trend indicates a cluster-type of distribution pattern. The landslides are concentrated mainly in the gullies and streams, and there is a high probability that landslides will continue to occur there in the future.